Secure Key Distribution Using Fragmentation and Assimilation in Wireless Sensor and Actor Networks. (27th September 2015) - Ghafoor, AtaUllah; Sher, Muhammad; Imran, Muhammad; Derhab, Abdelouahid
Secure key distribution is one of the most important building blocks to ensure confidentiality in wireless sensor and actor networks (WSANs). However, the key distribution becomes a challenging task when keys have to be relayed by compromised nodes in order to establish secure communication between distant nodes. To deal with this issue, we propose in this paper a key distribution scheme, named key distribution using fragmentation and assimilation (KDFA). In this scheme, the sender node splits the actual key into fragments and sends them through intermediate actor nodes towards the receiver node. The latter assimilates these key fragments using XOR operation to reconstruct the actual key. In this case, attacker cannot retrieve the actual key and only gets the key fragment. KDFA is composed of two parts: (a) key distribution protocol (KDP) to distribute the key using intra-actor and interactor communication scenarios and (b) key fragmentation algorithm (KFA) to slice the key using binary calculations. KDFA execution has been specified and formally verified using Rubin logic. Moreover, the performance and the resilience of the proposed protocol are further analyzed through extensive simulations using ns-2.35. Results show that KDFA is resilient against actor node compromise and key exposure.